ANALISIS DAMPAK KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU DALAM SISTEM ZONASI - Wahira; Ahlun Ansar; Sawal Hidayat (Irfani, 2025)
This study aims to examine the positive and negative impacts of the New Student Admission (PPDB) policy based on the zoning system and to analyze the 2025 New Student Admission System (SPMB) policy as a response to the challenges of zoning implementation. The approach used is a literature study based on 43 sources, including scholarly journals, academic articles, theses, and educational regulations from the period 2018–2025. The analysis was conducted using content analysis techniques. The findings indicate that: (1) The zoning system positively contributes to equal access to education, cost efficiency due to proximity of residence, a more equitable student distribution, and increased community participation. (2) However, the policy also brings negative impacts such as disparities in school quality, manipulation of residential data, weak policy dissemination, and the marginalization of high-achieving students. (3) As a response, the 2025 SPMB policy introduces a more accountable approach through four admission pathways: administrative domicile, affirmative action, academic achievement, and relocation. SPMB also grants greater autonomy to local governments and applies digital verification and integration with the national civil registry (Dukcapil) database. This study concludes that while the zoning system provides a foundation for educational equity, SPMB is expected to address inequalities and promote a fairer and more transparent student admission process. Keywords: PPDB, Zoning System, Policy Impact, SPMB 2025, Educational Equity.